Pengaruh Country of Origin, Brand Familiarity, Dan Kepercayaan Terhadap Keputusan Pembelian Smartphone Samsung Di Kota Padang - Astra Prima Budiarti; Yasri Yasri; Erni Masdupi (Jurnal Praktik Bisnis, 2019)
The research is proposed to determine the influence of country of origin, brandfamiliarity, and trust towards consumers of Samsung smartphone purchase decision in Padang. The population in this research were the Padang citizens who do not have smartphone. The number 100 respondens as research sample is determined by using Hair formula and elected by using purposive sampling techniqe. Primary and secondary data are used in this research. Analysis data technique is using path analysis dan hypotesis test by using t test with SPSS version 21.0 is used to analyzed the data. The result of this research shows that the country of origin and brand familiarity are positively and significantly affect consumer trust. Furthermore, country of origin, brand familiairty, and trust all together have a significant influence to purchase decision but individually only brand familiarity and trust that have a significant and positive effect to purchase decision.